PENGARUH DIMENSI KUALITAS PELAYANAN JASA TERHADAP KEPUASAN DAN MINAT DATANG KEMBALI KONSUMEN PADA DEALER WIRA MEGAH TOYOTA PROFITAMAS PALANGKA RAYA - Isra Misra; Arianto Arianto (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2018)
This research aims to see the Influence of Service Quality Dimension on Satisfaction and Consumers' Cause Back Against The Wira Megah Car Workshop Toyota Profitamas Palangka Raya Branch.This research is a quantitative research using descriptive quantitative approach. Analysis tool in this research is Smart PLS (Path Analysis) application. The research variables consist of Quality of Service (X), Consumer Satisfaction (Y1) and Come Back (Y2) as mediation variable. Samples use Accidental Sampling method as many as 100 samples from all customers of Toyota Workshop Palangka Raya.Result of research of service quality constructively can influence customer's satisfaction which have implication on intention come back in accordance with outer loading analysis result 0,867 (86,7%). Similarly, customer satisfaction variables have been able to explain and mediate quality of service variables with outer loading of 0.925 (92.5%). While for the intention variable comes back own value of outer loading equal to 0,922 (92,2%) The information indicate that statistically test service of new service to workshop is the highest indicator in describing variable of intention come back again.